TRAINING RESIDENTIAL STAFF TO CONDUCT TRIAL‐BASED FUNCTIONAL ANALYSES1. Issue 1 (20th February 2013) - Lambert, Joseph M.; Bloom, Sarah E.; Kunnavatana, S. Shanun; Collins, Shawnee D.; Clay, Casey J.
Abstract We taught 6 supervisors of a residential service provider for adults with developmental disabilities to train 9 house managers to conduct trial‐based functional analyses. Effects of the training were evaluated with a nonconcurrent multiple baseline. Results suggest that house managers can be trained to conduct trial‐based functional analyses with a high degree of procedural fidelity.